Hairy Cell Leukemia and Bladder Cancer in a Patient: Relation with Dye Exposure and Review of the Literaure - Semra Paydas (Advances in Hematology)
Chemical exposure is important in the etiology of some cancers. Dye or solvent exposures are important both in bladder cancer (BC) and hairy cell leukemia (HCL). Here a case with BC and HCL has been presented and literature has been reviewed.